5-HTTLPR genotype and anxiety-related personality traits: A meta-analysis and new data - Munafò, Marcus R.; Freimer, Nelson B.; Ng, Whitney; Ophoff, Roel; Veijola, Juha; Miettunen, Jouko; Järvelin, Marjo-Riitta; Taanila, Anja; Flint, Jonathan (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2009)
We investigated the strength of evidence for association of the 5‐HTTLPR polymorphism and the personality trait of Harm Avoidance. We used new primary data from a large sample of adults drawn from the Finnish population. We also applied meta‐analytic techniques to synthesize existing published data. The large number of studies of the 5‐HTTLPR polymorphism allowed us to apply a formal test of publication bias, as well as formally investigate the impact of potential moderating factors such as measurement instrument. Univariate ANOVA of primary data (n = 3,872), with 5‐HTTLPR genotype as a between‐groups factor, indicated no evidence of association with Harm Avoidance (P = 0.99). Meta‐analysis indicated no evidence of significant association of 5‐HTTLPR with Harm Avoidance (d = 0.02, P = 0.37), or EPQ Neuroticism (d = 0.01, P = 0.71), although there was evidence of association with NEO Neuroticism (d = 0.18, P < 0.001). Our analyses indicate that the 5‐HTTLPR variant is not associated with Harm Avoidance. Together with our previous analyses of a large sample of participants with extreme Neuroticism scores (defined by the EPQ), we have data that excludes a meaningful genetic effect of the 5‐HTTLPR on two measures of anxiety‐related personality traits. There remains the possibility that the variant influences the NEO personality questionnaire measure of Neuroticism. However, a large, well‐powered primary study is required to test this hypothesis directly and adequately. © 2008 Wiley‐Liss, Inc.